Negotiating Piety and Image: Prewedding Photography, Islamic Legal Norms and Cultural Change - Try Subakti; Siti Partiah; Jihan Amalia Syahidah; Falikh Ramadhani Bin Taib (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2026)
This study aims to analyze the construction of religious eliteâ€™s views on the practice of pre -wedding photography, the factors that influence these differences in views, and the forms of negotiation of Islamic law in responding to the development of visual culture. The study uses an empirical legal method with a socio-legal approach. Data were obtained through in-depth interviews with fifteen purposively selected religious figures, including kiai, ulama, religious organization administrators, and Islamic law academics in Pamekasan Regency, and supported by literature studies. Data were analyzed qualitatively using Max Weber's theory of authority, Horikoshi and Dhofier's concept of religious elites, and the perspective of negotiation of Islam and modernity from Eickelman and Piscatori. The results show three typologies of views: total rejection, conditional tolerance, and moderate adaptation. These differences reflect variations in the legal istinbÄá¹ method which is based on a textual approach (nash), ijtihad based on maá¹£laá¸¥ah and maqÄá¹£id al-syarÄ«'ah, as well as consideration of ' urf as a social reality. This study finds that religious elites not only act as guardians of orthodoxy but also as mediators negotiating sharia norms with modern visual culture through a contextual process of fiqh production. These findings enrich contemporary Islamic legal studies on the transformation of religious authority in Muslim societies in the digital era.